A highly efficient prediction of delamination migration in laminated composites using the extended cohesive damage model. (15th January 2017) - Li, X; Chen, J
Abstract: The extended cohesive damage model (ECDM) has been recently developed by authors for predicting multicrack failure mechanism in fibre materials. The ECDM is Partition of Unity Method (PUM) based and is a condensed FEM formulation through eliminating the enriched degree of freedoms (DoFs) for nonlinear fracture analysis. To account for the cohesive crack effect, an equivalent damage scalar relating to strain filed is introduced in terms of energy dissipation during the post-failure process to characterize the damage evolution. The ECDM is capable of characterizing discontinuity with conventional DoFs only, thus it is significantly efficient in modelling multicrack propagation. This paper investigates the performance of the ECDM through single element tests as well as modelling the delamination migration in laminated composites. Detailed comparison with experimental work and standard cohesive zone model (CZM) is carried out. This investigation shows the ECDM exhibits excellent efficiency and accuracy compered to CZM. The ECDM can reduce the CPU time in prediction of delamination migration of a laminated composite specimen by more than 90% compared to CZM. Therefore, the ECDM is a robust computational approach for highly efficient predicting delamination migration in laminated composites.